Challenges and Opportunities in Digital Screening for Hypertension and Diabetes Among Community Groups of Older Adults in Vietnam: Mixed Methods Study - Trang Thi Thu Nong; Giang Hoang Nguyen; Alexander Lepe; Thuy Bich Tran; Lan Thi Phuong Nguyen; Jaap A R Koot (JMIR Publications, 2024)
BackgroundThe project of scaling up noncommunicable disease (NCD) interventions in Southeast Asia aimed to strengthen the prevention and control of hypertension and diabetes, focusing on primary health care and community levels. In Vietnam, health volunteers who were members of the Intergenerational Self-Help Clubs (ISHCs) implemented community-based NCD screening and health promotion activities in communities. The ISHC health volunteers used an app based on District Health Information Software, version 2 (DHIS2) tracker (Society for Health Information Systems Programmes, India) to record details of participants during screening and other health activities. ObjectiveThis study aimed to assess the strengths, barriers, and limitations of the NCD screening app used by the ISHC health volunteers on tablets and to provide recommendations for further scaling up. MethodsA mixed methods observational study with a convergent parallel design was performed. For the quantitative data analysis, 2 rounds of screening data collected from all 59 ISHCs were analyzed on completeness and quality. For the qualitative analysis, 2 rounds of evaluation of the screening app were completed. Focus group discussions with ISHC health volunteers and club management boards and in-depth interviews with members of the Association of the Elderly and Commune Health Station staff were performed. ResultsIn the quantitative analysis, data completeness of all 6704 screenings (n=3485 individuals) was very high. For anthropomorphic measurements, such as blood pressure, body weight, and abdominal circumference, less than 1% errors were found. The data on NCD risk factors were not adequately recorded in 1908 (29.5%) of the screenings. From the qualitative analysis, the NCD screening app was appreciated by ISHC health volunteers and supervisors, as an easier and more efficient way to report to higher levels, secure data, and strengthen relationships with relevant stakeholders, using tablets to connect to the internet and internet-based platforms to access information for self-learning and sharing to promote a healthy lifestyle as the strengths. The barriers and limitations reported by the respondents were a non-age-friendly app, incomplete translation of parts of the app into Vietnamese, some issues with the tablet's display, lack of sharing of responsibilities among the health volunteers, and suboptimal involvement of the health sector; limited digital literacy among ISHC health volunteers. Recommendations are continuous capacity building, improving app issues, improving tablet issues, and involving relevant stakeholders or younger members in technology adoption to support older people. ConclusionsThe implementation of the NCD screening app by ISHC volunteers can be an effective way to improve community-led NCD screening and increase the uptake of NCD prevention and management services at the primary health care level. However, our study has shown that some barriers need to be addressed to maximize the efficient use of the app by ISHC health volunteers to record, report, and manage the screening data.